2014
DOI: 10.14453/aabfj.v8i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Financial Capability and Effectiveness: Exploring Financial Counsellors’ Perspectives

Abstract: The financial capability of the community has become a topical issue in recent years around the globe. The role financial education plays improving financial capability is recognised by the G20 countries. With a plethora of programs, workshops, seminars and other resources available in the community, we find that there is little research that measures the impact/usefulness of these programs including what should be included in such programs. This study seeks to contribute to the understanding of the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…However, not every person is willing to use the relevant products or services in the same way. Moreover, the market for financial services is becoming increasingly complex and complicated, and the responsibility for taking financial decisions rests solely on the individual making choices in this regard (Vyvyan et al, 2014). Meanwhile, a number of studies have shown that the state of personal finances, economic prosperity and financial behaviours differ significantly between men and women (Fisher, 2010;Theodos et al, 2014;Chen & Volpe, 2002;Lusardi & Mitchell, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, not every person is willing to use the relevant products or services in the same way. Moreover, the market for financial services is becoming increasingly complex and complicated, and the responsibility for taking financial decisions rests solely on the individual making choices in this regard (Vyvyan et al, 2014). Meanwhile, a number of studies have shown that the state of personal finances, economic prosperity and financial behaviours differ significantly between men and women (Fisher, 2010;Theodos et al, 2014;Chen & Volpe, 2002;Lusardi & Mitchell, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from that, sometimes what the teenager's demand is beyond their parents' capability to provide as their fund source, that can lead to a new economy problem in the family.The matter whether someone is consumptive or not is a result of the minimum financial knowledge (financial literacy). Along with that, some researchers have shown that financial literacy has a significant impact on one's financial behavior [1,2,3]. Someone who has low financial literacy usually has a financial problem in his life.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that guidance is provided to individuals based on their personality traits for resolving an unidentified situation. Thereby, it has been validated that the risk tolerance will be highly observed among younger potential investors as compared to the expert potential investors (Vyvyan et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…According to Vyvyan, Blue, and Brimble (2014), personality is the core construct of behaviors, motives, feelings, and thoughts for every individual. It demonstrates as a combination of perceptual, cognitive, and differentiating motivational and emotional attributes (Netemeyer, Warmath, Fernandes, & Lynch Jr, 2018).…”
Section: Introductionmentioning
confidence: 99%